2022
DOI: 10.3389/fnmol.2022.902572
|View full text |Cite
|
Sign up to set email alerts
|

Artesunate Alleviates Paclitaxel-Induced Neuropathic Pain in Mice by Decreasing Metabotropic Glutamate Receptor 5 Activity and Neuroinflammation in Primary Sensory Neurons

Abstract: Experimental studies on the pathogenetic process of paclitaxel-induced neuropathic pain (PINP) have been initially carried out, but PINP still has no effective therapy. Recently reported studies have highlighted the involvement of glutamate receptors and neuroinflammation in peripheral and central nociceptive transmission in PINP. Artesunate is a first-line antimalarial drug with established efficacy in alleviating pain in a variety of pathologies. The current work assessed whether artesunate inhibits PINP by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 79 publications
0
3
0
Order By: Relevance
“…Spontaneous pain, which is not triggered by external stimuli, presents a considerable hurdle in the management of chemotherapy-induced neuropathic pain [ 33 ]. Patients suffering from spontaneous pain may experience a range of debilitating symptoms that significantly affect their quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…Spontaneous pain, which is not triggered by external stimuli, presents a considerable hurdle in the management of chemotherapy-induced neuropathic pain [ 33 ]. Patients suffering from spontaneous pain may experience a range of debilitating symptoms that significantly affect their quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…These routes are most commonly used for pain management with analgesics [65]. However, beyond pain management, the intrathe-cal route is widely used for stem cell therapy [45,46,62,67,68], gene therapy [7,17,38,68], delivery of immune cells [63], sedation [41], protein therapy, insulin delivery [69], mineral delivery [70], chemical delivery [2,[70][71][72], and drug therapy using agonists [43,72,73], antagonists [43,64], antibiotics [70,74], and antiparasitic drugs [75] (Table 6). Intraspinal injection used in pain models can be divided into cancer pain models [68], including chemotherapy, induced pain models [5,75], and non-cancer pain models, such as models of arthritis [24], rheumatoid arthritis [72], diabetes-induced neuropathic pain [69,73], chronic pancreatitis-induced pain [19], spinal injury-induced pain [57,60], post-herpetic neuralgia [43], foraminal stenosis-induced pain [2,3], chronic DRG compression-induced pain [45], spared nerve injury [76], intrathecal capsaicin-induce...…”
Section: Uses and Application Of Epidural And Intrathecal Injectionmentioning
confidence: 99%
“…Recent study indicated that artesunate could promote osteoblast differentiation through miR-34a/DKK1/Wnt pathway [14]. Besides, artesunate alleviated paclitaxelinduced hyperalgesia and spontaneous pain by decreasing DRG mGluR5 expression and neuroin ammation in the mouse model of paclitaxel-induced neuropathic pain [15].Due to the permeability of BBB, artesunate is a promising candidate for therapy CNS disease more than the cerebral malaria. In CNS, artesunate reduced the severity of experimental autoimmune encephalomyelitis by inhibiting migration of pathogenic T cells to the CNS [16].…”
Section: Introductionmentioning
confidence: 99%